The Addams family [videorecording (DVD)] - Tiernan, Greg; Vernon, Conrad; Vernon, Conrad; Addams, Charles, 1912-1988 (Universal Pictures Home Entertainment, 2020)
When the Addams family moves to a new neighborhood, Wednesday forms a friendship with the daughter of a conformist reality television show host.